First report of Plesiomonas shigelloides as opportunistic pathogen in tilapia Oreochromis niloticus (Linnaeus, 1758) in a fish farm in Lima, Peru - Sierralta Chichizola, Verónica (2016)
The presence of Plesiomonas shigelloides causing enteric disease in tilapia Oreochromis niloticus in a fish farm in Lima region, Peru is reported. The bacteria were isolated and identified as Plesiomonas shigelloides by conventional biochemical techniques and confirmed by the API 20NE system (numerical profile 7162744 that ratifies 99.3% P. shigelloides). Strains evaluated (n=4) had a fermentative metabolism of glucose, test positive to cytochrome oxidase, indole, Voges-Proskauer and methyl red. The most frequent external signs were erythema in abdomen and pectoral fins, and prominent and reddened anus with bloody discharge. Internally, ascites in visceral cavity and gut inflammation were detected. Histopathology studies revealed edema of the lamina propia and epithelial necrosis of gastric and intestinal tissue, and necrosis in anterior kidney and gonad.